STATISTICAL HYPOTHESIS TESTING USING FUZZY LINGUISTIC VARIABLES - Iuliana Carmen BĂRBĂCIORU (Fiabilitate şi Durabilitate)
This work proposes a fuzzy statistical test of fuzzy hypotheses usinglinguistic variables. The method is based on Zadeh’s principle: the fuzzy population mean in the null hypothesis is converted to fuzzy numbers using conversion scales proposed by Chen and Hwang (1992). The method proposed by Chen et al [10] reflects thereal situation than conventional methods